Dampak Pembangunan Pedestrian di Pantai Air Manis Kota Padang dalam Rangka Kunjungan Wisatawan ke Objek Wisata Pantai Batu Malin Kundang - Fernando Fernando; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study describes the impact of the development of pedestrians on the beach of Air Manis, Padang City on the increase in the number of visits to the Batu Malin Kundang beach tourism object. The author uses a theoretical concept based on Mill's opinion in the basis of tourism theory about the impact of developing tourist attractions. Descriptive analysis is the research method used and purposive sampling technique is used in determining research informants. By collecting data using interview, observation, and documentation techniques. The results of this study explain that with the development of a pedestrian on the air manis beach, the city of padang, increased tourist visits at Batu Malin Kundang beach tourism object because this pedestrian creates a new attraction for the air manis beach tourism area so it can also improve the economy of the people of Air Manis village. Even so, this development also produces environmental impacts such as poor cleanliness and the creation of water pollution near the Malin Kundang stone monument.